Hapten-mediated recruitment of polyclonal antibodies to tumors engenders antitumor immunity - Brett Schrand; Emily Clark; Agata Levay; Ailem Rabasa Capote; Olivier Martinez; Randall Brenneman; Iris Castro; Eli Gilboa (Nature Communications, 2018)
Efficient tumor antigen uptake by dendritic cells is facilitated by antibody coating of tumor cells. Here, the authors develop an approach based on hapten vaccination and hapten/tumor targeting ligand conjugates that potentiate anti-tumor immunity by generating and redirecting serum antibodies to tumors.